2010
DOI: 10.1161/circimaging.109.934273
|View full text |Cite
|
Sign up to set email alerts
|

Reduced End-Systolic Pressure-Volume Ratio Response to Exercise

Abstract: Background-Limitations in the predictive value of negative exercise echocardiography in type 2 diabetes mellitus has been linked to a reduced end-systolic pressure-volume response (ESPVR). We sought whether abnormal ESPVR reflected subclinical diabetic heart disease by examining the association between the ESPVR and markers of myocardial dysfunction and to establish if the change (⌬) or peak systolic blood pressure/end-systolic left ventricular volume ratio (SP/ESV) is a better marker of contractile reserve in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, previous studies have shown exaggerated diastolic and systolic dysfunction in response to stress in patients with diabetes. 46,47 Subjecting our participants to a third stress protocol (in addition to leg exercise during the acquisition of 31 P-MRS and adenosine stress for the assessment of MPRI and oxygenation SIΔ) was deemed too high a burden on study subjects as this would lead to significantly longer adenosine infusion times, higher risk of adverse event rates, and high drop-out rates. For the same reasons, we have not carried out invasive coronary angiography for the assessment of endothelium-dependent coronary vasodilatation and vascular smooth muscle cell responsiveness.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, previous studies have shown exaggerated diastolic and systolic dysfunction in response to stress in patients with diabetes. 46,47 Subjecting our participants to a third stress protocol (in addition to leg exercise during the acquisition of 31 P-MRS and adenosine stress for the assessment of MPRI and oxygenation SIΔ) was deemed too high a burden on study subjects as this would lead to significantly longer adenosine infusion times, higher risk of adverse event rates, and high drop-out rates. For the same reasons, we have not carried out invasive coronary angiography for the assessment of endothelium-dependent coronary vasodilatation and vascular smooth muscle cell responsiveness.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In asymptomatic patients with aortic stenosis the ΔESPVR could be calculated during stress, but the trans aortic systolic pressure drop should be added to the brachial systolic pressure to correctly calculate the ESPVR both at rest and at peak stress. Different normal vs abnormal ΔESPVR cut-off-values have been observed for different stressors such as exercise [6,15,18,23,25,27,28], subclinical heart disease in diabetes [19,28], to donor hearts not eligible for heart transplant [17,26,29]. A systematic review of the literature with meta-analysis was needed to identify all published papers examining the use of ΔESPVR (PVR) for the prediction of cardiac death and/or heart failure hospitalization in patients with resting LV dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In an another paper by Jellis et al [28], in subclinical diabetic heart disease the ΔESPVR is relatively poorly associated with standard echocardiographic measures of myocardial dysfunction such as calibrated integrated backscatter, strain, and strain rate. The disparity between the ΔESPVR and echocardiographic parameters of myocardial dysfunction is likely because individual markers of LV dysfunction identify different pathological processes occurring concurrently within the spectrum of diabetic heart disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation